Insuring the Future. (1st November 2001) - Lynch, T.; Wells, D.
Abstract : Environmental politics needs more than piecemeal institutional efforts and more than calls for a set of 'new' values. It needs a realistic, comprehensive, and effective policy programme. Such a programme can be derived from a conjunction of Hardin's work on the 'tragedy of the commons' and Beck's analysis of the 'risk society', and involves exploiting the possibilities for the internalisation of risk provided by the insurance and reinsurance industries. Such exploitation requires tailored changes to the politico-legal environment, enforcing strict liability for the production of risk, permitting any and all agents adversely effected by such negative externalities to initiate action for damages. The aim is not to clog up social and economic life with endless legal disputation, but through such a threat to ensure that environmentally significant investment and productive strategies are actively constrained by actuarially calculated strategies for risk internalisation.